Bimetallic and plasmonic Ag-Au on TiO2 for solar water splitting : an active nanocomposite for entire visible light region absorption - Patra, Kshirodra K.; Gopinath, Chinnakonda S. (Chemcatchem, 2016)
The current study demonstrates a potential method for maximum utilization of the entire visible light region of the solar spectrum by designing a plasmonic-metals semiconductor composite. A combination of Ag+Au nanoclusters would broaden the visible-light absorption at least between 400 and 650nm. This hypothesis was evaluated through solar water splitting (SWS) activity of Au-TiO2, Ag-TiO2, and Ag on Au-TiO2 (AgAuT) composites. AgAuT bimetallic nanocomposite shows the maximum apparent quantum yield of 3.3% with hydrogen generation (718molh.g(-1)) from aqueous methanol, and overall water splitting activity (7molg.h(-1), AQY=0.04%) under one sun conditions. Enhanced photocatalytic activity of AgAuT is partly attributed to the formation of hot electrons. A thin layer of Ag coating on Au particles leads to a core-shell morphology with Au in the core. Fermi level equilibration between metal and titania, and Schottky junction formation are directly demonstrated. The strong electronic interaction between Ag and Au, and with TiO2 is evident from its electron rich character and confirmed by Raman spectroscopy, X-ray photoelectron spectroscopy, photoluminescence, and high-resolution TEM measurements. Electronic factors seem to be responsible for the high rate of hydrogen production.